Tendencias del traslado de actividades en las manufactureras en Puerto Rico y el título de propiedad sobre la planta física, 2005-2011 - Doris Morales; Ahmad H. Juma'h; Antonio Llorens-Rivera; Félix Cue; Ángel Ruiz (Atlantic Review of Economics, 2012)
– This study shows the pattern of manufacturers in Puerto Rico which have closed or relocated somewhere else, and their relationship with governmental incentives to set up those plants in governmental buildings over the period 2005-2011. Data was obtained from statistical reports on manufacturers from the Workforce Development Administration belonging to Puerto Rico Labor Department. The information regarding property deeds (land and building) was obtained from statistical reports on rental files from Puerto Rico Industrial Development Company. Data suggests that companies have been relocated to different countries in the last few years, either to countries with intensive workforce (e.g. Mexico and Dominican Republic) or intensive technology (e.g. Singapore and Canada). Moreover, multinationals's work transfer have a significant impact on the re-evaluation of the incentive strategy for economic growth in Puerto Rico. Over 50% of the companies which have transferred/closed operations had that type of incentives. This means that strategies involving incentives on building rentals are not strong enough to retain manufacturers in Puerto Rico.
Keywords: 330; closing operations; work transfer; property deeds (land and building); relocation